Risk distribution and benefit analysis of PPP projects based on public participation - Wang, Yinglin; Gao, Ruolan (International Journal of Strategic Property Management, 2020)
This paper aims to formulate a new PPP project public-participation mechanism that uses “public satisfaction” as a direct influencing factor in conjunction with the public-private benefit model to achieve a substantial response from project stakeholders regarding public satisfaction and ensure the transparency of PPP project operation. The proposed model, combined public satisfaction assessment with the principal-agent model, investigates the influence of public satisfaction on investors’ efforts and the benefit or risk distribution between the government and private investors. The results show that the public’s satisfaction level with the project directly affects the proportion of public and private income distribution, which provides a way for the public to directly play a substantive and positive role in PPP projects to guarantee public benefits and the smooth implementation. The increase in the public satisfaction evaluation of either the government or the investors, helps improve the overall effectiveness of PPP projects.